Glass specification & physical sample for spandrel glass CW1-6 (RFA-02_Rev C) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.